Multidisciplinary management of placenta accreta spectrum in Lebanon: a model for improving outcomes - El Hajj, Houssein; El Kassis, Nadine; Abdelkhalek, Yara; Moubarak, Malak; Atallah, David (International journal of gynecological cancer, 2025)
To achieve successful outcomes through cesarean hysterectomy, surgeons must adopt a strategic approach that prioritizes the prevention of urologic injuries, employs techniques for controlling difficult bleeding and, when suitable, considers conservative management options.4 To address this, the gynecologic oncology team at Hôtel-Dieu de France University Hospital in Beirut has developed a structured multidisciplinary protocol for managing patients with placenta accreta spectrum. Over the years, this model has successfully led to standardized approaches in the management of placenta accreta spectrum, focusing on collaborative care involving obstetricians, gynecologic oncologists, and other healthcare professionals in a multidisciplinary approach.7 The group has been active in organizing educational initiatives, such as workshops and conferences, to share knowledge and promote this collaborative practice. Data collection or acquisition and analysis: HEH, NK, YA, MM. Writing the manuscript or report: HEH, DA, MM. Review and editing: HEH, DA, MM, YA, NK.